Genome-wide protein QTL mapping identifies human plasma kallikrein as a post-translational regulator of serum uPAR levels - Portelli, Michael; Siedlinski, Mateusz; Stewart, Ceri E.; Postma, Dirkje S.; Nieuwenhuis, Maartje A.; Vonk, Judith M.; Nurnberg, Peter; Altmuller, Janine; Moffatt, M.F.; Wardlaw, Andrew J.; Parker, Stuart G.; Connolly, Martin J.; et al. (Federation of American Society of Experimental Biology, 2014)
The soluble cleaved urokinase plasminogen activator receptor (scuPAR) is a circulating protein detected in multiple diseases, including various cancers, cardiovascular disease, and kidney disease, where elevated levels of scuPAR have been associated with worsening prognosis and increased disease aggressiveness. We aimed to identify novel genetic and biomolecular mechanisms regulating scuPAR levels. Elevated serum scuPAR levels were identified in asthma (n=514) and chronic obstructive pulmonary disease (COPD; n=219) cohorts when compared to controls (n=96). In these cohorts, a genome-wide association study of serum scuPAR levels identified a human plasma kallikrein gene (KLKB1) promoter polymorphism (rs4253238) associated with serum scuPAR levels in a control/asthma population (P=1.17×10−7), which was also observed in a COPD population (combined P=5.04×10−12). Using a fluorescent assay, we demonstrated that serum KLKB1 enzymatic activity was driven by rs4253238 and is inverse to scuPAR levels. Biochemical analysis identified that KLKB1 cleaves scuPAR and negates scuPAR's effects on primary human bronchial epithelial cells (HBECs) in vitro. Chymotrypsin was used as a proproteolytic control, while basal HBECs were used as a control to define scuPAR-driven effects. In summary, we reveal a novel post-translational regulatory mechanism for scuPAR using a hypothesis-free approach with implications for multiple human diseases.